Applications of Click Chemistry in the Development of HIV Protease Inhibitors - Mudgal, Mukesh M. (Int J Med Chem, 2018)
Acquired Immunodeficiency Syndrome (AIDS) has been devastating for millions of people around the world. Inhibition of the human immunodeficiency virus (HIV) protease is among the most important approaches for the therapeutic intervention in HIV infection. Since the discovery of the HIV-1 protease, this enzyme has been considered as a key target for the inhibition of viral replication. A large body of research has been done to develop an effective HIV-1 protease inhibitor. There are to date 10 HIV-1 protease inhibitor drugs approved by the Food and Drug Administration (FDA) that have improved the survival and quality of life of HIV infected people. These drugs are prescribed in combination with the reverse transcriptase inhibitors, which is referred to as highly active antiretroviral therapy (HAART). The HIV-1 protease inhibitors play a vital role in HAART. The applications of click chemistry are dispersing in the field of drug discovery. Recently, click chemistry has captured a lot of attention and has become a powerful tool for the synthesis of medicinal skeletons in the discovery of anti-HIV drugs. Click reaction is a well-known method for making carbon−heteroatom−carbon bonds. Click reactions are popular because they are wide in scope, of high yielding, quick to perform, and easy to purify. In this review, we outlined current approaches towards the development of HIV-1 protease inhibitors employing click chemistry.